Coping with Stress Strategies among HIV Positive Patients: A Qualitative Content Analysis - Maryam Mahmoudi; Tahereh Dehdari; Davood Shojaeezadeh; Ladan Abbasian; Seeyd Saleheh Mortazavi (Zanjan University of Medical Sciences and Health Services, 2014)
Background and Objectives: Patients with HIV/AIDS have different experiences regarding coping with stress. Understanding these experiences is essential to design tailored interventions. The aim of this study was to explore experiences of patients with HIV on coping with stress strategies. Materials and Methods: In this qualitative content analysis study, 26 participants with HIV were selected using purposive sampling from counseling of behavioral diseases center, Imam Khomeini hospital in Tehran in 2012. In-depth semi-structured interviews were used to collect data during nine months. The transcripts were analyzed using the Diekelmann's method. Results: The participants were aged 20 to 73 years. Analyzing the data emerged two themes including emotional-based coping strategy with two sub-themes including adaptive and maladaptive coping strategy and the problem-based coping strategy with three sub-themes including seeking education and counseling, medication adherence and healthy life style. Conclusion: Clarification and explanation of coping with stress strategies can be used to design and implement effective intervention for reducing stress in patients with HIV/AIDS.